2020
DOI: 10.5194/gmd-2019-370
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Can high-resolution GCMs reach the level of information provided by 12–50 km CORDEX RCMs in terms of daily precipitation distribution?

Abstract: In this study, we perform an evaluation of PRIMAVERA high-resolution (25-50 km) Global Climate Models (GCMs) relative to CORDEX Regional Climate Models (RCMs) over Europe (12-50 km resolutions). It is the first time such assessment is performed for regional climate information using ensembles of GCMs and RCMs at similar horizontal resolutions. We perform this exercise for the distribution of daily precipitation contributions to rainfall bins over Europe 25 under current climate conditions. Both ensembles are e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…In addition, the importance of the resolution of climate models to simulate spatial and temporal mean regional climate change in specific regions could be further elucidated when comparing high-resolution GCMs with RCMs, including analysing the influence of the better resolved large scale forcing. This was to some extent done in a study over Europe and could possibly be extended over some of the regions investigated in this study (Demory et al 2020). Also, in the case of the low radiative forcing of the RCP2.6 scenario, the RCMs follow the CCS of the driving CORDEX-CORE GCMs quite closely.…”
Section: Discussionmentioning
confidence: 62%
“…In addition, the importance of the resolution of climate models to simulate spatial and temporal mean regional climate change in specific regions could be further elucidated when comparing high-resolution GCMs with RCMs, including analysing the influence of the better resolved large scale forcing. This was to some extent done in a study over Europe and could possibly be extended over some of the regions investigated in this study (Demory et al 2020). Also, in the case of the low radiative forcing of the RCP2.6 scenario, the RCMs follow the CCS of the driving CORDEX-CORE GCMs quite closely.…”
Section: Discussionmentioning
confidence: 62%
“…However, we cannot reach this conclusion based solely on this analysis, since we examine only a single model, which may not be representative of other models, and because the range of resolutions considered may be too narrow. Demory et al (2020) and Strandberg and Lind (2020) found that PRIMAVERA GCM simulations and EURO-CORDEX simulations at comparable resolution simulated fairly similar precipitation frequency-intensity distributions, which would agree with a limited influence of upscaling. However, a number of studies do find improvements in the large-scale circulation with resolution, including for extratropical cyclones and storm tracks (Colle et al, 2013;Jung et al, 2006Jung et al, , 2012Zappa et al, 2013), Euro-Atlantic weather regimes (Dawson et al, 2012(Dawson et al, , 2018Cattiaux et al, 2013;Strommen et al, 2019;Fabiano et al, 2020), and blocking (Jung et al, 2012;Anstey et al, 2013;Matsueda et al, 2009, Berckmans et al 2013Schiemann et al, 2017Schiemann et al, , 2020Davini et al 2017a, b;Dawson and Palmer, 2020; see also Introduction).…”
Section: Discussionmentioning
confidence: 76%
“…In GCMs, global precipitation tends to increase with resolution, and for grid point GCMs (as opposed to spectral GCMs) the fraction of land precipitation and moisture fluxes from land to ocean increases, largely due to better resolved orography (Vannière et al, 2019;Terai et al, 2018;Demory et al, 2014). Precipitation extremes tend to get heavier and in some studies agree better with observational estimates with increased resolution (Wehner et al, 2010;O'Brien et al, 2016;Kopparla et al, 2013;Shields et al, 2016;Vannière et al, 2019;Demory et al, 2020;Strandberg and Lind, 2020), unless the parameterization schemes are not suited to the resolution (e.g. Wehner et al, 2014, andpossibly Bador et al, 2020, who found worse performance in higher-resolution versions of multiple GCMs whose parameterizations were not retuned at higher resolution, particularly in the tropics).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Through dynamical and empirical-statistical downscaling more detailed simulations at the European level are provided, although depending on the boundary conditions of low resolution global climate models. In the evaluation of precipitation by Demory et al (2020) the high-resolution global climate simulations (25-50 km) from PRIMAVERA are compared to the CORDEX regional climate simulations (12-50 km) over Europe. The effect of increasing resolution from 50 km to 12 km is small outside mountainous and coastal regions (Demory et al, 2020).…”
Section: Atmospherementioning
confidence: 99%